2011
DOI: 10.1007/s10067-011-1699-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hyperuricemia in Bangkok population

Abstract: To investigate the prevalence of hyperuricemia in general Thai population and to evaluate its association with metabolic syndrome. A total of 1,945 subjects who sought for routine annual health checkup in our hospital from 1 October 2009 to 31 March 2010 were enrolled into the study. Inclusion criteria were healthy individuals, aged ≥35 years old, and lived in Bangkok for over 10 years. Data of general health status, age, gender, history of alcoholic consumption, body weight, height, and waist circumference we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 27 publications
6
53
2
1
Order By: Relevance
“…In patients with manifest atherosclerosis, both presence of more than three metabolic risk factors and the presence of a high waist circumference are associated with increased risk of future type 2 diabetes [15]. Some case series studies [16,17] reported that the prevalence of metabolic syndrome was high among patients with gout. Moreover, hyperuricemia has been associated with metabolic syndrome in studies [18][19][20] of both healthy individuals and patients.…”
Section: Hyperuricemia With Metabolic Syndromementioning
confidence: 98%
See 1 more Smart Citation
“…In patients with manifest atherosclerosis, both presence of more than three metabolic risk factors and the presence of a high waist circumference are associated with increased risk of future type 2 diabetes [15]. Some case series studies [16,17] reported that the prevalence of metabolic syndrome was high among patients with gout. Moreover, hyperuricemia has been associated with metabolic syndrome in studies [18][19][20] of both healthy individuals and patients.…”
Section: Hyperuricemia With Metabolic Syndromementioning
confidence: 98%
“…It may also precipitate cardiovascular diseases for which the metabolic syndrome is a strong risk factor. The most different in the prevalence of hyperuricemia was found in male adults with metabolic syndrome compared with nonmetabolic syndrome [17] and higher prevalence of metabolic syndrome was also found in men with hyperuricemia [17]. Even in those with normouricemia, higher serum uric acid levels were associated with metabolic syndrome [21 & ].…”
Section: Hyperuricemia With Metabolic Syndromementioning
confidence: 98%
“…Previous studies have demonstrated that the prevalence of MetS was high among patients with gout [11]. Other authors have claimed that, even healthy individuals, hyperuricemia was associated with MetS [12].…”
Section: Introductionmentioning
confidence: 99%
“…10 Another large study in Bangkok population showed that prevalence of hyperuricemia is 24.4%. 11 According to these studies prevalence of hyperuricemia is significantly higher in patients with acute stroke than normal population. These findings are consistent with our study as patients with hyperuricemia were more in stroke patients as compared to control group.…”
Section: Discussionmentioning
confidence: 99%